Cost-Minimization Analysis of Antibiotic Therapy in Pneumonia Patients - Lailis, Nurlailis Sa'adah (AACENDIKIA: Journal of Nursing, 2024)
Pneumonia, a severe lung infection caused by various pathogens, poses a significant global health challenge and is associated with high mortality rates. In the Special Region of Yogyakarta, respiratory infections are a leading cause of illness. This study aims to identify patient characteristics and evaluate antibiotic therapies and cost-efficiency at RSUD Yogyakarta in 2023. Utilizing a descriptive observational design and Cost Minimization Analysis (CMA), the study found that ceftriaxone injection is the most cost-effective single antibiotic therapy (Rp5,858,567), while the combination of Mei Act Capsules + fosmycin injection is the most economical combination therapy (Rp2,832,524). These findings highlight the importance of selecting antibiotic therapies that are not only effective but also cost-efficient, in order to enhance pneumonia treatment quality while reducing financial burdens.